Methanolic rhizome extract of Trillium govanianum coated gold nanoparticles: Facile biogenic synthesis, their characterisation, and potential antimicrobial study - Khaleeq‐Uz Zaman; Jehan Bakht; Adil A.H. Mujawah; Abdur Rauf; Muhammad Sharif; Aneela Maalik (Micro & Nano Letters, 2022)
Abstract The scientific community is endowed with the essential biogenic, eco‐benign, and cost‐effective synthesis of gold nanoparticles (AuNPs) of least explored Trillium govanianum methanolic extract. The study involved T. govanianum selection based on its tremendous therapeutic properties. These AuNPs were characterised by UV–visible spectroscope, atomic force electron microscope, scanning electron microscope (SEM), FTIR spectroscope, and X‐ray diffraction. The atomic force electron microscope pattern revealed that particle size ranges from 2 to 24.3 nm which corresponds to X‐ray diffraction analysis data (8.87–15 nm) with spherical morphology. The spherical nature, particle size distribution, non‐agglomeration, and homogeneity of AuNPs were also studied from SEM image. The diameter range of AuNPs was measured between 20 and 30 nm with an average size of 25 nm. FTIR profile showed that AuNPs were stabilised and capped by bio‐molecules containing aromatic amine functional groups. Amongst C. albicans, Curvularia, R. oryzae, A. niger, A. alternaria, and Paecilomyces fungal strains, AuNPs were found most efficient against C. albicans (53.33%) at 18 μL per disc. While in P. aeroginosa, B. subtilis, E. coli, K. pnemoniae, S. aureus, and X. compestris bacterial strains, AuNPs at 18 μL per disc revealed promising antibacterial potential against P. aeroginosa by displaying maximum inhibition of 66.66 %.